Cerebral Vasculitis in Crohn's Disease: Always a Complication of Inflammatory Bowel Disease or Tumor Necrosis Factor–Alpha Inhibition?. Issue 12 (27th September 2019) - Moser, Tobias; Bubel, Nele E; Machegger, Lukas; Pikija, Slaven; Sellner, Johann
Abstract : Cerebral vasculitis may be a complication of Crohn's disease (CD) or a side-effect of therapies with biologics including tumor-necrosis factor-alpha antibodies. Here, we report a case of progressive brainstem syndrome and cranial polyneuritis in a patient with CD who had been treated with infliximab. We identified Lyme neuroborreliosis (LNB) as the cause of cerebral vasculitis and ischemic stroke and observed a favorable course following antibiotic treatment. Our case highlights the need for extensive search of causes of cerebral vasculitis in patients with CD and treatment with biologics.